Physicochemical properties, volatile compound profile changes, and sensory evaluation of meatballs with the addition of different vegetable peels - Zor, Melek; Erdemir, Ebru; Fettahoğlu, Kübra; Topdaş, Elif Feyza; Şengül, Memnune (Italian Journal of Food Science, 2025)
This study aimed to determine the phenolic and antioxidant capacities of potato (Solanum tuberosum L.) and squash (Cucurbita pepo L.) peels, which are kitchen waste products, and to investigate their potential use in improving the physicochemical properties of meatballs, a meat product. Potato and squash peel powders were separately added to the meatball formulation at a rate of 6%. Meatballs with 6% breadcrumbs were used as the control group (C). Moisture content, color values (L*, a*, b*), pH, TBARS value, cooking loss, volatile compound profile, and sensory qualities of meatballs cooked in a pan with a small amount of olive oil were determined. When the color values of the meatballs were examined, the L* values of those containing vegetable peel powder (VPP) were lower than those of the control group. While the lowest average a* value was observed in the samples with squash peel powder, the highest average a* value was recorded in the control group. The pH of the meatballs with squash peel powder was higher than that of the other two groups. The TBARS values of the meatballs ranged between 0.30 and 1.80 mg MDA/kg, and increased with the addition of vegetable waste to the meatball formulation. The cooking loss values of the meatballs prepared with VPP were higher compared to those with breadcrumbs. As a result of GC-MS analyses, a total of 61 compounds were detected in the raw and cooked meatball samples. The number of compounds identified in cooked meatballs was lower than in the raw meatball dough. Among the compound groups in the meatballs, the highest number belonged to the terpene group, which included 19 compounds. Principal component analysis (PCA) clearly demonstrated that the volatile compound compositions of cooked and uncooked meatball samples differed. Based on the results obtained in this study, it can be concluded that the use of VPP in meatball production positively influenced the evaluated properties. VPP can serve as a substitute for breadcrumbs, thereby contributing to waste valorization and enhancing the waste utilization and sensory properties of the final product.